2022
DOI: 10.4103/njcp.njcp_1598_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with dry eye disease among adults in a population-based setting in South-West Nigeria

Abstract: Background: Dry eye disease (DED) occurs as a result of an abnormality in tear production, tear consistency, and tear evaporation. Aim: The aim of this study is to determine the prevalence and risk factors associated with dry eye disease in a population-based setting in Southwest Nigeria. Patient and Methods: A cross-sectional study was conducted at a medical outreach at Iperu Remo in Nigeria. A systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The association might be due to nearly similar mean age in study participants of that of Mexico, Ghana and this study. However, a study that was held in South-West Nigeria 32 indicated that those who had been on ophthalmic drops prior to the study were found to be 4% less likely diagnosed with dry eye. This discrepancy might be due to the double utilisation of spectacles by the study participants in that conducted in Nigeria when compared with the current study.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The association might be due to nearly similar mean age in study participants of that of Mexico, Ghana and this study. However, a study that was held in South-West Nigeria 32 indicated that those who had been on ophthalmic drops prior to the study were found to be 4% less likely diagnosed with dry eye. This discrepancy might be due to the double utilisation of spectacles by the study participants in that conducted in Nigeria when compared with the current study.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, this study revealed a higher prevalence of SDE when compared with a systematic review and meta-analysis in China (17%) 7 and the research outcomes reported in the USA (6.8%), 25 in Brazil 4 (12.8%), in Open University in Thailand (17.5%), 26 in university students in Bangkok, Thailand (8.15%), 13 in Indonesia (27.5%), 9 in Singapore (12.3%), 10 in India (40.9%), 27 in Philippines (22.9%), 28 in Malaysia secondary referral hospital (33.8%), 29 in Saudi Arabian population (32.1%), 30 in Lebanon (36.4%), 31 in South-West Nigeria (28.2%) 32 and in South Nigeria (27.4%). 33 The discrepancy across the study outcomes might be due to differences in the study period and data collection tools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to McCarty et al and Uchino et al, the estimated prevalence of DED varies widely and ranges from 5.5% to 73.5% [ 7 , 8 ]. This dramatic variation in the prevalence of DED can possibly be attributed to the lack of standardized diagnostic criteria as well as the controversy about the accuracy of the known diagnostic tests [ 1 , 9 ]. Because of that, the National Eye Institute Workshop has done much research and tests to standardize and unite the way of diagnosing DED.…”
Section: Discussionmentioning
confidence: 99%